Evaluasi Praktik Pinjaman Online melalui Pendekatan Maqasid al-Syari’ah dalam Perspektif Hukum Islam - Sara Mutammima Rohmati; Fathudin; Fitrotul Khasanah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
The phenomenon of online lending (pinjol) has rapidly expanded as a quick financing solution but often involves high-interest rates, late penalties, and unethical collection practices. This study aims to evaluate online lending using the Maqasid al-Shariah approach within the framework of Islamic law, focusing on the protection of religion (hifzh al-din), life (hifzh al-nafs), intellect (hifzh al-‘aql), lineage (hifzh al-nasl), and property (hifzh al-mal). Employing a normative-qualitative method through the analysis of DSN-MUI fatwas, OJK regulations, and empirical data from social cases of borrowers in Indonesia, the study reveals that conventional online lending practices generate widespread mafsadah (harm). Documented cases include mental distress leading to suicide, family breakdowns due to debt pressure, and property loss from excessive interest and penalties. These findings indicate that online lending contradicts all key objectives of Maqasid al-Shariah, producing more harm than benefit. Therefore, the study recommends developing Sharia-compliant lending models that emphasize transparency, fairness, and mutual assistance to promote social justice and economic well-being.